Utilizing Social Media to Study Information-Seeking and Ethical Issues in Gene Therapy - Robillard, Julie M; Whiteley, Louise; Johnson, Thomas Wade; Lim, Jonathan; Wasserman, Wyeth W; Illes, Judy (JMIR Publications, 2013)
BackgroundThe field of gene therapy is rapidly evolving, and while hopes of treating disorders of the central nervous system and ethical concerns have been articulated within the academic community, little is known about views and opinions of different stakeholder groups. ObjectiveTo address this gap, we utilized social media to investigate the kind of information public users are seeking about gene therapy and the hopes, concerns, and attitudes they express. MethodsWe conducted a content analysis of questions containing the keywords "gene therapy" from the Q&A site "Yahoo! Answers" for the 5-year period between 2006 and 2010. From the pool of questions retrieved (N=903), we identified those containing at least one theme related to ethics, environment, economics, law, or society (n=173) and then characterized the content of relevant answers (n=399) through emergent coding. ResultsThe results show that users seek a wide range of information regarding gene therapy, with requests for scientific information and ethical issues at the forefront of enquiry. The question sample reveals high expectations for gene therapy that range from cures for genetic and nongenetic diseases to pre- and postnatal enhancement of physiological attributes. Ethics questions are commonly expressed as fears about the impact of gene therapy on self and society. The answer sample echoes these concerns but further suggests that the acceptability of gene therapy varies depending on the specific application. ConclusionsOverall, the findings highlight the powerful role of social media as a rich resource for research into attitudes toward biomedicine and as a platform for knowledge exchange and public engagement for topics relating to health and disease.